Efficacy of branched-chain amino acid to increase muscle strength in chronic heart failure patients: an evidence-based case report - Karin Wiradarma; Lily Indriani Octovia (World Nutrition Journal, 2020)
Background: Chronic heart failure (CHF) patients can fall into cardiac cachexia (CC), which is marked by the decrease of muscle mass and strength. Cardiac cachexia decreases the functional capacity and quality of life also increases the length of stay, medical fees, complications, and mortality rate. Branched-chain amino acid (BCAA) accounted for 35% of amino acids that build the muscle. We hope that BCAA supplementation can increase muscle strength of CHF patients, especially the elderly who is more prone to fall into CC. Thus, we performed an evidence-based case report to seek an opportunity of BCAA supplementation to an elderly with CHF.Objectives: To determine the efficacy of BCAA supplementation on increasing muscle strength in CHF patients.Methods: Literature searching of the evidence-based case report was performed on Pubmed, Cochrane, and Scopus according to the clinical query. Screening on title, abstract, and full text was done based on eligibility criteria (meta-analysis or clinical trials, suitability to clinical questions, English language, full-text availability, and human studies), followed by duplication filter and critical appraisal.Results: A randomized-controlled trial was found, but it didn’t find a significant difference between the experimental and control groups.Conclusions: BCAA supplementation doesn’t give a significant improvement in muscle strength in CHF patients.